2016
DOI: 10.1007/s10903-016-0365-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Church-Based, Culturally Tailored Program to Promote Completion of Advance Directives Among Asian Americans

Abstract: Background Having an Advance Directive (AD) can help to guide medical decision-making. Asian Americans (AA) are less likely than White Americans to complete an AD. This pilot study investigated the feasibility and efficacy of a church-based intervention to increase knowledge and behavior change related to AD among Chinese and Vietnamese Americans. Methods This study utilized a single group pre- and post-intervention design with 174 participants from 4 churches. Domain assessed: demographics; AD-related knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…The study also found that the odds of designating a SDM were higher for older adults who had stayed in the United States for 10 years or more, had English proficiency, and had a high level of acculturation into mainstream U.S. culture. These results supported our predictions and were consistent with previous studies (Dobbs et al., 2015; Jang et al., 2017; Sun et al., 2017). There is a great potential that older Asian Americans who have stayed in the United States longer, speak English fluently, and have higher level of acculturation may have adopted Western values and beliefs (i.e., patient autonomy and self-determination) and have applied these values to their EoL decision-making process.…”
Section: Discussionsupporting
confidence: 94%
“…The study also found that the odds of designating a SDM were higher for older adults who had stayed in the United States for 10 years or more, had English proficiency, and had a high level of acculturation into mainstream U.S. culture. These results supported our predictions and were consistent with previous studies (Dobbs et al., 2015; Jang et al., 2017; Sun et al., 2017). There is a great potential that older Asian Americans who have stayed in the United States longer, speak English fluently, and have higher level of acculturation may have adopted Western values and beliefs (i.e., patient autonomy and self-determination) and have applied these values to their EoL decision-making process.…”
Section: Discussionsupporting
confidence: 94%
“…ACP has been successfully promoted in faithbased community organizations for Black and Asian American populations, although these programs have not been widely implemented and may not reach entire communities. [47][48][49] Our results underscore the importance of community-based strategies tailored to the needs of unique neighborhoods-to reach all community-dwelling older adults living in underresourced or disadvantaged communities. 29 Given the complex etiology of health disparities and the sociocultural influences on end-of-life decision-making, 50 it is important to consider community-based factors contributing to ACP disparities.…”
Section: Discussionmentioning
confidence: 68%
“…Although we used the weights provided by data set to reduce sampling bias, the potential for a lack of representativeness is unavoidable. Also, potential direct contributors on ACP completion such as knowledge about the ACP (e.g., Sun, Bui, et al, 2016) or previous exposure to the EOL care (e.g., Jang et al, 2010) were not included in the analysis models due to the limitation of data. In addition, regarding EOL treatment, the data we used considered two specific conditions: experience of severe pain and loss of physical and/or cognitive function.…”
Section: Discussionmentioning
confidence: 99%